5(-4q-16)-7q=13+19-11q

Simple and best practice solution for 5(-4q-16)-7q=13+19-11q equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(-4q-16)-7q=13+19-11q equation:


5(-4q-16)-7q=13+19-11q

We simplify the equation to the form, which is simple to understand
5(-4q-16)-7q=13+19-11q

Reorder the terms in parentheses
+(-20q-80)-7q=13+19-11q

Remove unnecessary parentheses
-20q-80-7q=+13+19-11q

We move all terms containing q to the left and all other terms to the right.
-20q-7q+11q=+13+19+80

We simplify left and right side of the equation.
-16q=+112

We divide both sides of the equation by -16 to get q.
q=-7

See similar equations:

| 6.4+1.8n=2.08 | | -12+5x=8-2x-6 | | 200-.5x=80 | | -1.3s+2.78=15.59+2.3s-2.9s | | 5(x+2)=2(x+2)+7 | | 42-8m=13m | | 34(18-4.5x)=16(4x-9)+61.6 | | -2(t+4.667)=9.5 | | -19.21+12.2g=0.9g | | 18-5y=3x-6 | | 35=5n+10 | | -11.3h-17.63=10.2h+18.92 | | 5(x+4.1)=10x-1.5 | | 8x+4(4x-3)=4(3x+4)-8 | | 13.5f+11.06+1.7f=10.34+17f | | 6x=171 | | 3a-15=-21 | | 7-(x+4)=34 | | 0.6(y-10)=0-y | | -18.9u=-18.1u+14.96 | | y-7=1.5x-6 | | y=x-17 | | 19+14j=17j-11 | | 3y-21=27 | | 6(x-1)-3=4x+2(-4+x) | | 45=300 | | 9(2r+4)=4(5r-1) | | 8(x+4)=2x+68 | | 7-g=6 | | 9.6t+6=30 | | 17m+3=14m | | 2x-11=6x+3 |

Equations solver categories